Kaiphas : der Hohepriester jenes Jahres : Geschichte und Deutung - Metzner, Rainer. (Ancient Judaism and Early Christianity, 2010)
The high priest Caiaphas is one of the important figures in biblical history who received little attention or sympathy in the judgement of posterity. Since the time of the old church the highest representative of the Jewish society in the time of Jesus was assessed as a wicked enemy of Jesus and the leading apostles in Jerusalem. This image obscures the religious and political efficiency of a man, who worked with great success in his office for a long period of eighteen years. What do we know about the historical Caiaphas? And what is the image of this man in the New Testament and afterwards? The present study tries to answer these questions in view of the history, the exegesis and the reception history. Der Hohepriester Kaiphas gehört zu den bedeutenden Figuren der biblischen Geschichte, denen im Urteil der Nachwelt eine geringe Aufmerksamkeit oder Sympathie entgegengebracht wurde. Seit der alten Kirche wurde der höchste Repräsentant des jüdischen Tempelstaates zur Zeit Jesu als bösartiger Feind Jesu und der führenden Apostel in Jerusalem betrachtet. Dieses Bild verdeckt die religiösen und politischen Leistungen eines Mannes, der achtzehn Jahre lang mit Erfolg amtiert hat. Was wissen wir über den historischen Kaiphas? Und welches Bild hat sich von ihm im Neuen Testament und in der Zeit danach ausgeprägt? Die vorliegende Studie versucht, diese Fragen historisch, exegetisch und wirkungsgeschichtlich zu beantworten.